2018
DOI: 10.1007/s00586-018-5739-1
|View full text |Cite|
|
Sign up to set email alerts
|

Can spinal surgery in England be saved from litigation: a review of 978 clinical negligence claims against the NHS

Abstract: The volume and costs of clinical negligence claims is threatening the future of spinal surgery. If spinal surgery is to continue to serve the patients who need it, most thorough investigation, implementation and sharing of lessons learned from litigation claims must be systematically carried out. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 6 publications
1
33
0
Order By: Relevance
“…Between 2013 and 2016, there were 131 claims relating to CES in the UK, with a projected value of 68 million. 34 These were most commonly due to delay in diagnosis or treatment. 34 In the US, the average payout of 15 lawsuits related to CES between 1983 and 2010 was $1.57 million.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2013 and 2016, there were 131 claims relating to CES in the UK, with a projected value of 68 million. 34 These were most commonly due to delay in diagnosis or treatment. 34 In the US, the average payout of 15 lawsuits related to CES between 1983 and 2010 was $1.57 million.…”
Section: Discussionmentioning
confidence: 99%
“…34 These were most commonly due to delay in diagnosis or treatment. 34 In the US, the average payout of 15 lawsuits related to CES between 1983 and 2010 was $1.57 million. 12 It is unknown whether the frequency of legal action for CES in a country is associated with the clinical threshold for investigation of symptoms with an MRI study, as all but one study of patients with suspected CES were carried out in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical litigation crisis poses a real and perhaps not widely recognised threat to the sustainability of the NHS—many clinicians, for example, are unaware of negligence claims in their own hospital 50. The four principles we have identified are supported by evidence, but, as in other countries, the benefits have been missed as a result of poor implementation 51.…”
Section: Discussionmentioning
confidence: 86%
“…20 Other studies determined that a lack of informed consent was the third most common reason for litigation, 11,13,14 while others found that litigation on grounds of lack of informed consent was less common. 12,26 One study found that a lack of informed consent was implicated in cranial cases more often than in spinal cases. 13 Median or mean payments were greater for plaintiff verdicts than for the settlements for spine surgery malpractice cases, 11,14 whereas payments for settlements were greater than those for plaintiff verdicts for endoscopic sinus surgery.…”
Section: Medicolegal Implications Of Informed Consentmentioning
confidence: 99%
“…12 Four studies examined spine surgery. 11,14,16,26 One of them determined that a lack of informed consent was the reason for the lawsuit in 42.6% of cases involving quadriplegia after cervical spine surgery in the United States, behind negligent surgery at 87.0% of cases and failure to diagnose or treat at 61.1% of cases, with total mean payments of $5.9 million for plaintiff verdicts and $2.8 million for settlements. 14 Another study found that a lack of informed consent was a factor in 24.4% of all spine surgery malpractice cases, as compared to a failure to diagnose at 31.6% of cases and a failure to treat at 32.7% of cases, with total median payments of $2.5 million for plaintiff verdicts and $1.3 million for settlements.…”
Section: Medicolegal Implications Of Informed Consentmentioning
confidence: 99%